Kapitał i zaufanie społeczne a aktywność obywatelska w Anglii i Polsce – implikacje dla edukacji obywatelskiej - Hejwosz-Gromkowska, Daria (Studia Edukacyjne, 2020)
Hejwosz-Gromkowska Daria, Kapitał i zaufanie społeczne a aktywność obywatelska w Anglii i Polsce – implikacje dla edukacji obywatelskiej [Capital and Social Trust vs. Active Citizenship in England and Poland – Implications for Civic Education]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 85-109. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.5 The aim of the paper is to analyze the tendencies of shaping both social capital and social trust in England and Poland. The analyses of aforementioned categories allow to explain the patterns of conventional civic participation. The social capital and social trust are also important factors influencing citizenship education. Therefore, analysis comprises policies towards citizenship education in English and Polish schools.